Konjunktiv ou Indicativo: quais fatores influenciam o uso dos modos no discurso reportado no alemão? - Costa, Andressa (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
In my research, I focus on the use of verbal mood in reported speech in German. For this purpose, I analyse a corpus of written language. In the introductory part of this paper I present theoretical aspects of the use of Konjunktiv in reported speech. In the first section the term reported speech is defined based on BÜHLER’s organon model of communication, SEARLE’s speech act theory and the concept of polyphony applied to the linguistics by DUCROT. Next, I describe the functions of reported speech in different text types and his signals. Section 2 is concerned with the variables verbal mood, communication verbs, tense of the communication verbs and types of complement clauses. The corpus and the method of analysis are described in the third section. The results and hypothesis are presented in section 4. The aspects that will be investigated are described concisely in the final part of this paper.